Detection of Anti-Platelet Glycoprotein Antibodies Using MAIPA Method - Hamidpour, Mohsen; Khalili, Ghader; Kamali, Mahin; Arzani, Mohammad Hasan; Jadali, Farzaneh; Alavi Majd, Hamid (Archives of Advances in Biosciences, 2010)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; color:red;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ascii-font-family:Calibri; mso-fareast-font-family:Calibri; mso-hansi-font-family:Calibri; mso-bidi-font-family:Arial;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->AITP mostly occur in children accompanied by variable clinical sings including petechiae, purpura, ecchymosis and severe bleeding. This study has determined and characterized the anti-platelet glycoproteins in children with ITP. The aim of this study was to determinate anti-platelet glycoproteins (GPs) using MAIPA method. During 18 months 38 children with clinical signs of AITP were studied in Mofid children hospital. To determine anti-platelet antibodies by ELISA technique, washed O negative platelets were used as a source of platelet antigens. MAIPA method was used to detect antibodies against individual platelet membrane glycoprotein. The anti-platelet antibodies level above mean+ 3SD of control group was assumed as positive. The results indicated that the platelet count ranges was between 2×109/L and 95×109/L. 63.5 % out of 38 patients were anti-platelet antibodies positive with ELISA method. The correlation between the above patients with anti-platelet antibody positive and clinical signs was 0.4. Results for determination of antibody against platelet GPIIb/IIIa, GPIb/IX and GPIa/IIa using MAIPA method were 44%, 51% and 25% respectively. In conclusion the preference of MAIPA method is the detection of very small amount of antibody. Since MAIPA is the specific method for the detection of antibody against glycoprotein antigens, it has the advantage of differentiating immune and non-immune thrombocytopenia.